Geomorphology of Scour Holes at Tidal Channel Confluences. Issue 6 (19th June 2018) - Ferrarin, Christian; Madricardo, Fantina; Rizzetto, Federica; Kiver, William Mc; Bellafiore, Debora; Umgiesser, Georg; Kruss, Aleksandra; Zaggia, Luca; Foglini, Federica; Ceregato, Alessandro; Sarretta, Alessandro; Trincardi, Fabio
Abstract : The morphology of scour holes at tidal channel confluences was investigated through high‐resolution acoustic mapping of the channel network in the Venice Lagoon (Italy). Our investigation identified 29 confluence scours ranging in depth from 7 to 26 m and characterized by different confluence geometry and scour properties. Scours were found at the confluence of two or more channels, having equal or unequal bed heights and a diverse confluence planform geometry. The main morphological characteristics of the scours were compared to literature data from fluvial environments. Like in rivers, the scour depth tends to increase with the angle of the confluence. Moreover, the maximum depth of the confluence scours in the Venice Lagoon is positively correlated with the tidal prism of the channels joining the confluence. The investigation of the seafloor features in the scour holes highlighted that, generally, small‐ and medium‐scale bedforms are present on the gentle slope. The scours' seafloor roughness indicated that in tidal channels both ebb and flood flows combine in shaping the confluence morphology. In addition, the analysis of historical bathymetric datasets dating back to the 1800s allowed us to analyze the morphological evolution of two of these erosive features. Our findings revealed the century‐scale morphological dynamics of scour holes, as a consequence of changes in the flow regime. Key Points: Twenty‐nine scours in a depth range between 7 and 26 m are found at tidal channel confluences in the Venice Lagoon Scour depth positively correlates to the tidal prism of the confluent channels Historical datasets revealed the century‐scale morphodynamics of these erosive features, as a consequence of changes in the flow regime